2008
DOI: 10.1007/s00453-008-9230-y
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of New and Known Online Packet Buffering Algorithms

Abstract: We present the first experimental study of online packet buffering algorithms for network switches. We consider a basic scenario in which m queues of size B have to be maintained so as to maximize the packet throughput. For this model various online algorithms with competitive factors ranging between 2 and 1.5 were developed in the literature. We first develop a new 2-competitive online algorithm, called HSFOD, which is especially designed to perform well under real-world conditions. In our experimental study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…Azar et al [5] gave a lower bound of 1.366 − Θ(1/m) for a deterministic algorithm for any B. Albers et al [3] showed that the competitive ratio of any greedy algorithms is at least 2 − 1/B− Θ(m −1/(2B−2) ) for any B and large enough m. They also gave a 17/9( 1.89)-competitive deterministic algorithm for B ≥ 2, and it is optimal in the case B = 2. Albers and Jacobs [2] performed an experimental study on several online algorithms for the multi queue model for the first time.…”
Section: Related Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Azar et al [5] gave a lower bound of 1.366 − Θ(1/m) for a deterministic algorithm for any B. Albers et al [3] showed that the competitive ratio of any greedy algorithms is at least 2 − 1/B− Θ(m −1/(2B−2) ) for any B and large enough m. They also gave a 17/9( 1.89)-competitive deterministic algorithm for B ≥ 2, and it is optimal in the case B = 2. Albers and Jacobs [2] performed an experimental study on several online algorithms for the multi queue model for the first time.…”
Section: Related Resultsmentioning
confidence: 99%
“…(iv) Before the first event of σ 3 , add T (T ) arrival events where arriving packets are destined for Q (1) , and the same number of arrival events where arriving packets are destined for Q (2) . Call these 2T (T) packets I-packets.…”
Section: Evaluating Smentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the algorithms described above were evaluated experimentally in the paper of Albers and Jacobs [2].…”
Section: Previous Workmentioning
confidence: 99%
“…Albers and Jacobs undertake an experimental evaluation of many of the following policies [AJ07,AJ10]. We note that with unit values, there is never a reason to preempt one packet in favor of another.…”
Section: Multiple Input Queuesmentioning
confidence: 99%